2015
DOI: 10.1590/1809-9823.2015.14163
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the two minute step test for diagnosis of the functional capacity of hypertensive elderly persons

Abstract: Objectives : To analyze the accuracy of the 2 minute step test in the diagnosis of the normal functional capacity (FC) of hypertensive elderly individuals or hypertensive elderly individuals with other associated chronic conditions (ACC). Methods : An observational diagnosis type study of 101 subjects, 41 of whom were hypertensive and 60 of whom were normotensive, was carried out. Receiver Operating Characteristic curves (ROC) were constructed based on the normal FC variable. Results : For hypertensive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…For this study, the number of right knee elevations for 2 min without running was counted and standardized. The minimum knee height, appropriate for the stride, was leveled at a midpoint between the patella and the anterosuperior iliac spine 11 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, the number of right knee elevations for 2 min without running was counted and standardized. The minimum knee height, appropriate for the stride, was leveled at a midpoint between the patella and the anterosuperior iliac spine 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Functional capacity may be negatively affected in individuals with OSA associated with fatigue, excessive sleepiness, excess weight, and low energy, which characterize the clinical presentation of the pathology 9 . Therefore, the 2-minute step test (2MST) appears as an alternative way to assess the functional capacity of an individual, considering that the ability to walk reflects the ability to maintain a series of activities of daily living in addition to enabling knowledge of the functional profile and the ability to guide decision-making in strategies aimed at preventing disabilities 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Muscular function and mobility will be evaluated using the Timed Up and Go test [ 29 ] and the 2-Minute Walk test [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…6,7 It was observed that the test was valid and had good sensitivity and specificity to evaluate the functional capacity of hypertension in the elderly, with and without associated chronic conditions. 8 Therefore, our research group proposed a 6-min stationary walk test associated with virtual reality (STVR-6). 9 Virtual reality integrates the user with a synthetic 3-dimensional environment, 10 creating an immersive and interactive virtual experience that occurs in real time.…”
Section: Introductionmentioning
confidence: 99%